Perceptions of Public Order Policing (POP) officials regarding the factors that escalate violence during protests in the Ekurhuleni, Johannesburg and Tshwane Municipal areas - Bezuidenhout, Christiaan (University of Pretoria, 2025)
Dissertation (MA (Criminology))--University of Pretoria, 2025.